Perceptions of COVID-19 among frontline health workers in Burkina Faso - Yaya Bocoum, Fadima; Kadio, Kadidiatou; Some, Télesphore; Ouedraogo, Adidjata; Drabo, Maxime; Kouanda, Seni (Frontiers in Sociology, 2023)
In Burkina Faso, the first cases of COVID-19 were reported in March 2020. Health personnel are on the front line of COVID-19 control, and it is important to understand their perceptions and knowledge of the disease. The objective was to determine the knowledge and perceptions of health care personnel of COVID-19 in the city of Ouagadougou. The study was conducted in five plots in the city of Ouagadougou. A total of 20 health workers from public and private health centers in the city of Ouagadougou were selected during May 2020. In-depth individual interviews were conducted, and a thematic analysis was performed using NVIVO. The routes of transmission identified were promiscuity, respiratory tract, and physical contact. Various symptoms have been noted, such as fever, cough, and runny nose. However, they recognize that these symptoms are not sufficient to make a diagnosis of COVID-19. Similarly, the treatments mentioned are modern medicine and phytomedicine. The research has generated information on health care workers' knowledge and perceptions of COVID-19. Therefore, they are useful for decision making regarding protective measures for health workers in the management of COVID-19.